Simple multi-wavelength imaging of birefringence:case study of silk - Honda, Reo (Sci Rep, 2018)
Polarised light imaging microscopy, with the addition of a liquid crystal (LC) phase retarder, was used to determine the birefringence of silk fibres with high (∼1 μm) spatial resolution. The measurement was carried out with the silk fibres (the optical slow axis) and the slow axis of the LC-retarder set at parallel angles. The direct fit of the transmission data allowed for high fidelity determination of the birefringence Δn ≈ 1.63 × 10(−2) (with ∼2% uncertainty) of the brown silk fibre, (Antheraea pernyi) averaged over the wavelength range λ = (425–625) nm. By measuring retardance at four separate wavelengths, it was possible to determine the true value of the birefringence of a thicker sample when an optical path may include a large number of wavelengths. The numerical procedures and required hardware are described for the do-it-yourself assembly of the imaging polariscope at a fractional budget compared to commercial units.